Development of Web-Based Learning Media for Matrix Operations and 4×4 Determinant Calculation with an Adaptation of the Sarrus Method - Pandiangan, Gus Rosauli; Zulfahmi Indra; Barus, Angelica; Simanulang, Mika Monica Fransiska (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2025)
The objective of this study is to develop a web-based learning tool that can be used for matrix operations (addition, subtraction, and multiplication) as well as for calculating the determinant of a 4×4 matrix. As an alternative to the complex cofactor method for determinant calculation, an adapted version of the Sarrus method is utilized. The research and development (R&D) process follows a digital learning media development approach, consisting of needs analysis, prototype design, implementation, and evaluation stages. This learning tool integrates basic matrix operations with an extended adaptation of the Sarrus method, incorporating A1, A2, and A3 components for 4×4 matrices. This method enables determinant calculations to be performed in a more systematic and efficient manner compared to the cofactor method, while basic matrix operations provide a comprehensive understanding of linear algebra. The study results indicate that an interactive web-based learning resource has been successfully developed. The tool features an integrated calculator for matrix addition, subtraction, and multiplication operations, as well as determinant calculations with step-by-step visualizations. The creation of this learning tool simplifies previously complex calculations while significantly improving time efficiency for both basic operations and determinant calculations.